REVITALIZING ABANDONED INFRASTRUCTURE: A COMPREHENSIVE FRAMEWORK FOR THE TRANSFORMATION OF ABANDONED BUILDINGS IN URBAN AREAS - Moh Suma Firman Romadhoni; Veronica C Amanda; Fido A Yanuar; Muhammad Farrel; Muh Rifki N Aprialdi (Department of Urban and Regional Planning, Faculty of Engineering, Universitas Brawijaya, 2025)
The phenomenon of abandoned buildings in urban areas creates significant aesthetic, economic and social challenges for the surrounding neighbourhood. The adaptive reuse strategy is emerging as an innovative solution that focuses on the reutilization of disused buildings through functional transformation for new purposes. This concept not only provides economic benefits through construction cost savings and increased property values, but also supports environmental sustainability by reducing material waste and preserving the historical value of architecture. This research emphasizes the importance of multi-stakeholder collaboration, policy integration, and the application of appropriate technology and design in the implementation of adaptive reuse by using the Systematic Literature Review (SLR) method to collect, identify and critically analyze, and present a literature review of studies relevant to a particular research question or discussion. By adopting such an approach, abandoned buildings can be transformed into productive assets that contribute to urban revitalization, provision of affordable housing, and improvement of the quality of living environment in modern cities.